LIFE INC: HOW THE WORLD BECAME A CORPORATION AND HOW TO TAKE IT BACK. - Bywater, Michael (New Humanist)
The article reviews the book "Life Inc.: How the World Became a Corporation and How to Take It Back," by Douglas Rushkoff.